If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -3 = -13 Reorder the terms: -3 + 2y = -13 Solving -3 + 2y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2y = -13 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = -13 + 3 2y = -13 + 3 Combine like terms: -13 + 3 = -10 2y = -10 Divide each side by '2'. y = -5 Simplifying y = -5
| 64/2x=24 | | 4(x-1)=-x-29 | | 12s-5s=3.5 | | 4q^2-7pq-9q+7p= | | 19t-1=4t+11 | | 2x+3=2x+x-2x-1 | | x-43=10 | | (4+3i)= | | 3x+1=x-19 | | 9w-8=6w-2 | | 6y(8y-4)= | | 4x+1=(5-x) | | (8n^2+41n+41)/(n+4) | | 9x-13y=8 | | 9x+13y=10 | | S=l-yl | | 9x+9y=225 | | X-13-x+2x=21 | | 8x+5y=-5 | | 2(x-4)-16=0 | | y=-8-0 | | 5(3w-2)-7= | | 6x-1(4x-1)=2 | | (d-4/4)^2=121 | | 5/3x2-x+19/9+0 | | 8x/4*3+2 | | c/-4+5=-9 | | 8y=-9 | | 200=a(120)+(-4) | | 200=a(120)+-4 | | -3=w+51 | | 200=a(120)+0 |